PENGGUNAAN MEDIA PEMBELAJARAN DALAM MENINGKATKAN PEMAHAMAN KONSEP IPAS KELAS 3 - Alvionita Moha; Sandi Budiana (STKIP Subang, 2024)
Based on the study conducted at SDN Layungsari 2, this research investigates the use of learning media to enhance third-grade students' conceptual understanding of Natural and Social Sciences (IPAS). The primary issue identified is the difficulty faced by students in grasping core concepts due to traditional teaching methods that rely heavily on lectures without engaging media. The purpose of this study is to evaluate the effectiveness of various learning media in improving students' comprehension of IPAS concepts. A qualitative approach was employed, utilizing observations, interviews, and document analysis to gather data from both students and teachers. The participants of this study were third-grade students at SDN Layungsari 2. The data was analyzed thematically to identify patterns and insights related to the use of learning media. The findings reveal that the integration of visual and interactive media significantly enhances students' understanding of IPAS concepts. The results also show that students are more engaged and motivated when learning materials are presented through multimedia tools. Additionally, teachers reported that the use of media facilitated better classroom management and more effective communication of complex concepts. In conclusion, the research indicates that the use of appropriate learning media in teaching IPAS can lead to improved educational outcomes for third-grade students.